Narratives of African American Women's Literary Pragmatism and Creative Democracy - Phipps, Gregory (Springer International Publishing, 2018)
This book charts an interdisciplinary narrative of literary pragmatism and creative democracy across the writings of African American women, from the works of nineteenth-century philosophers to the novels and short stories of Harlem Renaissance authors. The book argues that this critically neglected narrative forms a genealogy of black feminist intersectionality and a major contribution to the development of American pragmatism. Bringing together the philosophical writings of Maria Stewart, Anna Julia Cooper, and Mary Church Terrell and the fictional works of Jessie Fauset, Nella Larsen, and Zora Neale Hurston, this text provides a literary pragmatist study of the archetypes, tropes, settings, and modes of resistance that populate the narrative of creative democracy. Above all, this book considers how these philosophers and authors construct democracy as a lived experience that gains meaning not through state institutions but through communities founded on relationships among black women and their shared understandings of culture, knowledge, experience, and rebellion. .